Morphology of the seminal vesicle of Calomys callosus submitted to experimental chronic alcoholism - Martinez, M.; Mattos, E. C.T.; Mello, W.; Cagnon, V. H.A.; Martinez, F. E. (My University, 2001)
The objective of the present study was to assess the possible toxic effects of chronic alcohol ingestion on the ultrastructure of the lining epithelium of the seminal vesicle of the rodent Calomys callosus, in order to contribute to the understanding of the consequences of alcohol abuse for the morphology of the male reproductive apparatus. Twenty six adult animals aged three months were divided into two experimental groups. The control group received a solid diet (Purina chow) and tap water, and the alcoholic group received the same solid diet and ethanol P.A. diluted 20% in water (v/v). After 210 days of treatment, all animals were anaesthetised, weighed and sacrificed. At the end of treatment, mean body and seminal vesicle weight did not differ between control and alcoholic animals. The epithelial cells of the alcoholic group showed many alterations such as the presence of lipid droplets of different sizes, nuclei with increased peripheral chromatin and greater electrondensity, megamitochondria, and intense dilatation of the cisterns of the granular endoplasmic reticulum. It was concluded that 20% ethanol provokes marked ultrastructural lesions in the seminal vesicle.
Keywords: Alcoholism; Calomys callosus; Epithelium; Seminal vesicle